A framework to select innovations in patents to improve temporary edge protection systems in buildings - Nonnenmacher, Letícia (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2017)
This article presents a selection method of existing innovations in patents that propose improvements in Temporary Edge Protection Systems (TEPS). The method was divided into three stages. In stage 1, records were collected related to TEPS from the patent filing databases of the Instituto Nacional da Propriedade Industrial (National Institute of Industrial Property, Brazil), the United States Patent and Trademark Office and the European Patent Office. In stage 2, patents were selected based on the TEPS evaluation protocol created by Peñaloza, Formoso and Saurin (2017), which examines safety, efficiency and flexibility criteria. In stage 3, four patents were selected among the 20 patents found related to guard rails and three related to protection nets. Based on the results, one invention stands out that uses hollow posts in protection barriers, which allows for modular movement with safety and flexibility. The framework proposed in this research is a useful resource for disseminating techniques included in TEPS patent databases.